2016
DOI: 10.1007/s11368-016-1569-0
|View full text |Cite
|
Sign up to set email alerts
|

Soil properties and subsoil constraints of urban and peri-urban agriculture within Mahikeng city in the North West Province (South Africa)

Abstract: Purpose Urban and peri-urban agriculture is becoming increasingly important as a source of income and food for the urban population in South Africa. While most studies on urban agriculture have focused their attention on surface soils, there is dearth of information regarding subsoil properties. This study examined properties of subsoil horizons that may impede root growth and productivity of crops under urban agriculture. Materials and methods The properties of topsoil (0-20 cm) and subsoil horizons (20-40 cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Fertilisers are key inputs in the production of sufficient vegetable supplies to the African population. However, production efforts are compromised by acidic [4] and nutrient-poor soils, such as low phosphorus (P) levels [5].…”
Section: Introductionmentioning
confidence: 99%
“…Fertilisers are key inputs in the production of sufficient vegetable supplies to the African population. However, production efforts are compromised by acidic [4] and nutrient-poor soils, such as low phosphorus (P) levels [5].…”
Section: Introductionmentioning
confidence: 99%
“…In the North-West Province, the daily temperature is about 42°C during summer months and often −9°C during winter months [26]. According to [27], soil in this province is sandy loam and is classified as a Hutton form [28] or Rhodic Ferralsol [29] or Chromic Luvisol [30].…”
Section: Description Of the Study Sitesmentioning
confidence: 99%
“…The use of waste materials as an alternative to the consumption of natural resources in urban greening areas is presented in the paper by Yilmaz et al (2017) or specifically to enhance soil physical properties is shown in the contribution of VidalBeaudet et al (2017). Soils of peri-urban areas also are studied in three contributions, namely the one by Hernández-Martínez et al (2017) describing nitrogen dynamics in soils irrigated with untreated sewage effluents of Mexico City for more than a century, one by Wessolek et al (2017) showing the reclamation of former wastewater disposal fields of Berlin and one depicting subsoil constraints in urban and periurban regions of the small city of Mahikeng in South Africa (Materechera 2017).…”
mentioning
confidence: 99%